Effects of ribosomal exit tunnel on protein’s cotranslational folding - Thuy, Bui Phuong; Hoang, Trinh Xuan (Communications in Physics, 2013)
In vivo, folding of many proteins occurs during their synthesis in the ribosomeand continues after they have escaped from the ribosomal exit tunnel. Inthis research, we investigate the confinement effects of the ribosome on thecotranslational folding of three proteins, of PDB codes 1PGA, 1CRN and 2RJX,by using a coarse-grained model and molecular dynamics simulation. The exittunnel is modeled as a hollow cylinder attached to a flat wall, whereas aGo-like model is adopted for the proteins. Our results show that theexit tunnel has a strong effect on the folding mechanism by setting an order bywhich the secondary and tertiary structures are formed. For protein 1PGA, thefolding follows two different folding routes. The presence of the tunnel alsoimproves the foldability of protein.